2019
DOI: 10.3389/fnbeh.2019.00132
|View full text |Cite
|
Sign up to set email alerts
|

Infant Trauma Alters Social Buffering of Threat Learning: Emerging Role of Prefrontal Cortex in Preadolescence

Abstract: Within the infant-caregiver attachment system, the primary caregiver holds potent reward value to the infant, exhibited by infants’ strong preference for approach responses and proximity-seeking towards the mother. A less well-understood feature of the attachment figure is the caregiver’s ability to reduce fear via social buffering, commonly associated with the notion of a “safe haven” in the developmental literature. Evidence suggests this infant system overlaps with the neural network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 134 publications
(184 reference statements)
0
25
0
Order By: Relevance
“…This CORT blockade switches off the amygdala and the pup's fear response to threat, as well as the pup's fear learning: the infant rat pup's amygdala is uniquely dependent upon CORT to function (Barr et al, 2009; Moriceau, Wilson, Levine, & Sullivan, 2006). This buffering process wanes as pups mature and prepare for independence (Opendak et al, 2019; Robinson-Drummer et al, 2019). In humans, maternal presence during an aversive conditioning procedure has similarly been shown to block threat learning in children, with the strongest effects noted among children with the lowest CORT levels (Tottenham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This CORT blockade switches off the amygdala and the pup's fear response to threat, as well as the pup's fear learning: the infant rat pup's amygdala is uniquely dependent upon CORT to function (Barr et al, 2009; Moriceau, Wilson, Levine, & Sullivan, 2006). This buffering process wanes as pups mature and prepare for independence (Opendak et al, 2019; Robinson-Drummer et al, 2019). In humans, maternal presence during an aversive conditioning procedure has similarly been shown to block threat learning in children, with the strongest effects noted among children with the lowest CORT levels (Tottenham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of scarcity-adversity have also been used to experimentally demonstrate that environmental scarcity causally produces elevated CORT in mother rats and infant pups (Ivy, Brunson, Sandman, & Baram, 2008; Perry, Finegood, et al, 2019b; Raineki, Moriceau, & Sullivan, 2010; Raineki, Morgan, Ellis, & Weinberg, 2019), with subsequent disruption of neurobehavioral developmental outcomes (Avishai-Eliner, Gilles, Eghbal-Ahmadi, Bar-El, & Baram, 2001; Bale et al, 2010; Baram et al, 2012; Doherty, Blaze, Keller, & Roth, 2017; Junod, Opendak, LeDoux, & Sullivan, 2019; Perry et al, 2019a; Perry et al, 2019b; Perry et al, 2019c; Raineki, Rincón-Cortés, Belnoue, & Sullivan, 2012; Rincón-Cortés et al, 2015; Rincón-Cortés & Sullivan, 2016; Robinson-Drummer et al, 2019; Sevelinges et al, 2007; Walker et al, 2017). Taken together, these studies support the idea that chronically elevated CORT in infants and children may be one mechanism by which poverty-related adversity “gets under the skin” to influence child development.…”
Section: Introductionmentioning
confidence: 99%
“…For example, crEA (via parental separation and institutional caregiving) is followed by atypical responding of the amygdala and mPFC to parental cues (Callaghan et al, 2019b; Olsavsky et al, 2013). Rodent models of both abuse (fear conditioning) and insufficient bedding paradigms (which increase abusive physical treatment and decreased time with mother) have similarly been associated with altered neural responses to the mother in pups (Opendak et al, 2020; Raineki, Cortés, Belnoue, & Sullivan, 2012; Robinson-Drummer et al, 2019) – typically alterations in amygdala function appear developmentally earlier, which is then followed by aberrant responses in the mPFC responses at older ages (Robinson-Drummer et al, 2019). This last finding is consistent with the model presented in Figure 1 showing that the parental cue activates subcortical learning systems developmentally earlier than mPFC.…”
Section: Putting It All Together: Bridging Caregiving-related Schemasmentioning
confidence: 99%
“…Her group traced this effect to a temporary drop in dopamine in the basolateral complex when the mother was present (Barr et al, 2009). More recently, her group found that developmental maturation of the infralimbic cortex->amygdala pathway supplants this effect (Robinson-Drummer et al, 2019), such that "social buffering" by mother beyond the critical period induces a negative correlation between amygdala and VTA activation using PET imaging (Opendak et al, 2019). In contrast, maternal maltreatment due to resource scarcity closes the window such that maternal presence no longer deactivates amygdala within the critical period and at later ages maternal presence (perhaps appropriately) no longer deactivates the amygdala, nor does it produce the negative coupling of basolateral amygdala and VTA that would indicate convergent safety signals from BA25 and basomedial amygdala.…”
Section: Environmental Moderation Of Safety Learning: Influence Of Camentioning
confidence: 99%